Bio-attractant innovation with nano-gel technology to detect and control Silba adipata McAlpine on white cayenne peppers in Bali, Indonesia - Merta, I Ngurah Mega; Supartha, I Wayan; Susila, I Wayan; Parwata, I Made Oka A; Yuliadhi, Ketut Ayu; Purnomo, Purnomo (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Silba adipata is a new pest that attacks white chili pepper in Bali, Indonesia. Most farmers control this pest with synthetic insecticides although this method poses significant risks to human health and the environment. Therefore, innovations and control technologies that are environmentally friendly and sustainable are urgently needed. Preliminary results show that S. adipata frequently attacks local figs (Ficus variegata) in Bali. Dried figs (Ficus carica) have been reported to effectively attract S. adipata adults. This study aims to (1) determine the phytochemical compounds in F. variegata fruit extracts that have the potential to act as attractants for S. adipata during the process of searching for and locating host plants; (2) evaluate the effectiveness and efficiency of F. variegata fruit extract, nano fruit extract, and nanogel fruit extract as attractants for S. adipata on cayenne pepper plants. The methods used to achieve these objectives were (1) LC-MS/MS analysis for phytochemical profiling, and (2) a preference test to evaluate attractant efficacy. The results revealed that the phytochemical profile of F. variegata fruit extract includes 5-hydroxy-2-(4-hydroxyphenyl)-8,8-dimethylpirano[2,3-h]chromen-4-one, with the highest compound content (68.74%) in the fruit aged 9-16 weeks. The application of nanogel extract at a 50% concentration was highly effective and efficient as a biological attractant for S. adipata on white chilli plants in Bali. These findings strongly support the development of integrated pest management strategies in Indonesia.